2016
DOI: 10.1590/1806-9061-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Parameters and Histopathological Findings in the Forced Molt Laying Hens

Abstract: The aim of this study was to evaluate the effects of forced molting using biochemical parameters and histopathological findings in laying hens. 36 Hyline W36 strain laying hens, 90 weeks old were chosen for this research. Eight of these chickens were randomly selected and placed in a cage as the control group before the molting program began. All the others 28 chickens were used for the forced molting program. Eight laying hens were slaughtered at the end of the molting program named as molting group. The rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
2
5
0
4
Order By: Relevance
“…This results is similar to El-Kaiaty and Hassan (2004) who found no difference in calcium and phosphorous levels between three local breeds (Fayoumi, Golden Montazah and Matrouh).Moreover, Khawaja et al (2012) found no differences of calcium level between RIR, Fayoumi and Desi hens. The level of blood biochemical parameters of our study are comparable with those found by Mert and Yildirim (2016) however they are higher than that reported by Albokhadaim et al (2012) in Saudia Arabia chickens.…”
Section: Biochemical Parameterssupporting
confidence: 87%
“…This results is similar to El-Kaiaty and Hassan (2004) who found no difference in calcium and phosphorous levels between three local breeds (Fayoumi, Golden Montazah and Matrouh).Moreover, Khawaja et al (2012) found no differences of calcium level between RIR, Fayoumi and Desi hens. The level of blood biochemical parameters of our study are comparable with those found by Mert and Yildirim (2016) however they are higher than that reported by Albokhadaim et al (2012) in Saudia Arabia chickens.…”
Section: Biochemical Parameterssupporting
confidence: 87%
“…Molting was a physiological process taking place in adult birds as indicated by the change in feathers and the decrease in egg production (Mert and Yildirim, 2016). Regeneration and remodeling of the reproduction system took place during the molting process (Sundaresan et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Forced molting by fasting the chickens is used to shorten the resting period. There have been some studies of the forced molting of the layers of 66 weeks of age with refeeding and illumination regulation treatments (Fukuma and Ishibashi, 1997); of the layers of 90 weeks with the parameters of blood biochemicals and tissue histology (Mert and Yildirim, 2016); of the chickens of 1-1.5 years of age with the supplementation of snail flour feed (Kiptiyah et al, 2012); of the chickens of 84 weeks and 64 weeks of age with different molting treatments (Oguike et al, 2005); of the rejected chickens of 60-70 years of age with molting method and different feed composition and the parameter of the number of molted feathers (Fitroh et al, 2016). The study will use the forced molting of the postproduction chickens that are usually considered as broilers and sold in traditional markets.…”
Section: Introductionmentioning
confidence: 99%
“…No início do experimento, as aves foram submetidas à seleção, pesadas e distribuídas aleatoriamente em parcelas experimentais, compondo quatro grupos. Durante o período de indução da muda forçada, as aves receberam somente luz natural (adaptado de Yamauchi, 2007;Mert & Yildirim, 2016). Após esse período, introduziu-se luz artificial progressivamente até que atingisse 17 horas de luz ao dia (luz artificial + luz natural).…”
Section: Metodologiaunclassified
“…Os programas de muda forçada podem afetar as características histológicas do trato intestinal (Yamauchi, 2007;Mert & Yildirim, 2016), porém, os estudos que relacionam diferentes dietas com muda forçada são voltados, principalmente, para alterações histológicas do sistema reprodutivo (Koch et al, 2007;Mert & Yildirim, 2016) ou em dietas oferecidas em períodos não relacionados a muda forçada (Laudadio et al, 2012;Sun et al, 2012).…”
Section: Introductionunclassified